Faktor – Faktor yang Mempengaruhi Return on Asset PT. Bank Syariah Indonesia KCP Iskandar Muda - Sinuhaji, Endo Masika; Yanti, Nur Santri (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Analysis of profitability developments is one of the indicators carried out by banks to see or detect the magnitude of changes in the results of transactions carried out. Among them, measuring the level of profitability by measuring return on assets (ROA). The reason for using Return on Assets (ROA) to measure bank profitability is because Bank Indonesia, as a banking supervisor, prioritizes the profitability of a bank as measured by assets. Most of its funds come from public deposits. The higher the bank's profit, the better the bank's position on the use of assets. Therefore, ROA is used in this study as an indicator of the financial performance of Islamic banks. Keyword: Profitability, Return on Assets, Islamic Bank